Cutaneous TRPV4 Channels Activate Warmth-Defense Responses in Young and Adult Birds - Cristina-Silva, Caroline; Amaral-Silva, Lara; Santos, Kassia Moreira; Correa, Gabriela Monteiro; da Silva, Welex Candido; Fernandes, Marcia H. M. R.; da Silva, Glauber S. F.; Gargaglioni, Luciane H.; Almeida, Maria C.; Bicego, Kenia C. (Frontiers in Physiology, 2022)
Transient receptor potential vanilloid 4 (TRPV4) channels are sensitive to warm ambient temperatures (Ta), triggering heat loss responses in adult rats in a Ta range of 26°C to 30°C. In birds, however, the thermoregulatory role of TRPV4 has never been shown. Here, we hypothesized that stimulation of TRPV4 induces thermolytic responses for body temperature (Tb) maintenance in birds, and that this function is already present in early life, when the Ta range for TRPV4 activation does not represent a warm condition for these animals. We first demonstrated the presence of TRPV4 in the dorsal and ventral skin of chickens (Gallus gallus) by immunohistochemistry. Then, we evaluated the effects of the TRPV4 agonist, RN1747, and the TRPV4 antagonists, HC067047 and GSK2193874, on Tb and thermoeffectors at different Tas in 5-day-old chicks and 60-day-old adult chickens. For the chicks, RN1747 transiently reduced Tb both in thermoneutrality (31°C) and in a cold Ta for this phase (26ºC), which relied on huddling behavior inhibition. The TRPV4 antagonists alone did not affect Tb or thermoeffectors but blocked the Tb decrease and huddling inhibition promoted by RN1747. For the adults, TRPV4 antagonism increased Tb when animals were exposed to 28°C (suprathermoneutral condition for adults), but not to 19°C. In contrast, RN1747 decreased Tb by reducing metabolic rate and activating thermal tachypnea at 19°C, a Ta below the activation range of TRPV4. Our results indicate that peripheral TRPV4 receptors are functional in early life, but may be inhibited at that time when the range of activation ( 26°C to 30°C) represents cold Ta for chicks, and become physiologically relevant for Tb maintenance when the activation Ta range for TRPV4 becomes suprathermoneutral for adult chickens.